(untitled) (Research, Society and Development, 2021)
Due to the sedative and tranquilizer effects, the elderly use for longer than recommended, causing many unwanted effects, such as dependence. Around this, the objective of this work, by means of review, was to raise the causes of toxicology and dependence, in addition to understanding the management of drug withdrawal. Methodology: The SCIELO, LILICS, MEDLINE/PUBMED platforms and book were used, where they went through exclusion and inclusion criteria, resulting in 35 included studies. Results and Discussion: BZDs are generally safe drugs, but if used for short periods, being the most recommended for the elderly the use of BZDs with a short half-life. The great part of toxicology is cognitive and psychomotor, besides dependence. For the management of dependence, gradual reduction or assistance with other drug classes are used. Final considerations: The present study shows objectively and clearly the toxicology in the elderly, dependence and management of dependence, is one of the difficulties for the management the appearance of symptoms that resemble the return of the causes for the beginning of drug therapy.